Pentingnya Pembinaan Katekumen Dalam Gereja Katolik - Fransiska Akrianti Gea; Blasius Superma Yese; Dominikus Doni Ola (Journal New Light, 2024)
The preparation of this thesis began with the experience and observation of the author who saw and felt for himself various things of concern in catechumenal coaching. Catechumen coaching has not been done optimally, so the results are not optimal. Many catechumens are easily accepted or baptized into the Catholic Church, even though they do not yet have sufficient knowledge and depth of faith. In addition, after being accepted or baptized into the Catholic Church, there is no further formation. Though there are several stages or processes that must be done so that a person has a deep understanding of the Catholic faith before being accepted or baptized. The fault is not with catechumens, but on the part of the Catholic Church itself; Especially catechumens coaches and materials used in coaching. We all expect that a person who is accepted or baptized into the Catholic Church will have a firm faith and dare to bear witness in life.